T-Regulatory Link of the Immune System and Its Role in the Pathogenesis of Inflammation and Carcinogenesis of the Lungs - kobylyansky, Vyacheslav Ivanovich (Trends in Immunotherapy, 2025)
The lack of awareness among the general medical audience about the central link in the lung immune system―T-regulatory cells (Treg) and the existing contradictions on this issue necessitate consideration and analysis, which is the purpose of this work. An analysis of 63 full-text literary sources, selected from the primary information databases, was conducted. An assessment of Treg in maintaining immune status is provided, indicating that they play a central role in balancing proinflammatory and anti-inflammatory cytokines, thereby maintaining the body's homeostasis. Their primary function is reflected in the generally accepted paradigm underlying the diagnosis and treatment of immune system disorders, which consists of an immunosuppressive effect with complex, ambivalent manifestations. This effect limits inflammatory reactions, especially hyperergic ones, but simultaneously contributes to the suppression of the antitumor immune response and stimulation of carcinogenesis processes. A decrease in Tregs is associated with opposite effects that depend on the nature of the relationship between the tumor and inflammation, and requires immunoprecise therapeutic effects. By influencing Tregs, it is possible to target and effectively modulate the processes of inflammation and carcinogenesis in the lungs. The depletion of the T-regulatory cell population is directly proportional to antitumor activity and inflammation intensity, and inversely proportional to tumor progression and inflammation regression. The opinion of some researchers that depletion of Treg cells reduces inflammation is unfounded and contradicts the generally accepted paradigm.